2013
DOI: 10.3109/13693786.2012.688180
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Aspergillus fumigatus to caspofungin results in the release, and de novo biosynthesis, of gliotoxin

Abstract: Caspofungin is a member of the echinocandin class of antifungal agents that inhibit the synthesis of β 1,3 glucan thus disrupting fungal cell wall structure and function. Exposure of the Aspergillus fumigatus cultures to caspofungin (0.01, 0.1 or 1.0 μg/ml) resulted in a reduction in cell growth, but the production of the epipolythiodioxopiperazine toxin, gliotoxin, was comparable, or greater, in cultures exposed to caspofungin than untreated controls. Exposure of A. fumigatus hyphae to 1.0 μg/ml caspofungin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Another interesting finding was the increased production of the secondary metabolite fumagillin upon exposure of A. fumigatus to caspofungin. So far, only the release of the secondary metabolite gliotoxin has been reported for cultures of A. fumigatus in the presence of caspofungin [ 56 ]. Fumagillin has anti-angiogenic activity [ 57 ] and induces cell death in erythrocytes [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting finding was the increased production of the secondary metabolite fumagillin upon exposure of A. fumigatus to caspofungin. So far, only the release of the secondary metabolite gliotoxin has been reported for cultures of A. fumigatus in the presence of caspofungin [ 56 ]. Fumagillin has anti-angiogenic activity [ 57 ] and induces cell death in erythrocytes [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the fumagillin cluster during experimental animal infections has been detected, contributing to the invasion and generation of cell damage [40]. Other authors have shown that, in contact with caspofungin, fumagillin [87] and gliotoxin [88] are overexpressed. This implies that the treatment with caspofungin could have adverse effects on host cells during infection.…”
Section: Regulation Of Fumagillin Clustermentioning
confidence: 99%
“…β-(1,3)-D-Glucan synthase (GS) is a vital enzyme in the synthesis of the essential component of the fungal cell wall, β-(1,3)-D-glucan. Cells exposed to echinocandin B (shows morphological changes such as swelling and release of intracellular contents ( Eshwika et al, 2013 ). Echinocandins act as specific, non-competitive inhibitors of GS.…”
Section: Antifungal Treatment Strategiesmentioning
confidence: 99%